Usos y apropiaciones de la hipermedialidad e hipertextualidad en la construcción del reportaje multimedial a partir del trabajo realizado por los periodistas de los medios digitales semana.com y el tiempo.com (2011)
The present study analyzed the uses and appropriations of hypermedia and hypertext in construction of multimedia report, from the work of journalists in digital media Tiempo.com and Semana.com in 2011. Within the work, the reader will find as a major research findings that the trend in digital media in the country points to the development of multimedia reports, and report a successful reading requires proper use multimedia links hypertext, which extend the information to the user but also allow visual inspection of all elements that compose hypermedia, in conjunction with web site usability.